Energy-saving PET (Polyethylene Terephthalate) automobile roof and production process thereof

By combining the modified PET foam layer with the reinforcement, and using continuous foaming equipment and waste heat composite technology, the problems of energy waste and low production efficiency in the production process of traditional PET foam automobile roof are solved, and a lightweight, high-strength, energy-saving and efficient production process is achieved.

CN119898105AActive Publication Date: 2025-04-29YANTAI ZHENGHAI HIGH TECH

Patent Information

Application Number
CN202510392199.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The production process of traditional PET foam car roofs requires repeated heating and cooling, resulting in increased energy consumption and reduced production efficiency.

Method used

The modified PET foam layer is made by mixing and foaming with polyester and reinforcement (nanocellulose whiskers, modified carbon nanotubes and modified glass fibers), produced by continuous foaming equipment, and the adhesive film and the felt layer on the surface of the glass fiber are covered during the foaming process, and the composite process is completed using waste heat.

Benefits of technology

The lightweight and high strength of the PET car roof is achieved, while reducing the number of heating-cooling cycles, saving energy and improving production efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of automobile roof production, and particularly discloses an energy-saving PET automobile roof and a production process thereof. The energy-saving PET automobile roof comprises a fabric layer, an adhesive film, a glass fiber surface felt layer, a modified PET foam layer, a glass fiber surface felt layer, an adhesive film and a non-woven fabric layer which are sequentially connected, and the modified PET foam layer is prepared from, by weight, 45-60 parts of polyester and 2.95-5.61 parts of reinforcing agent. The reinforcing agent comprises nano cellulose whiskers, modified carbon nanotubes and modified glass fibers; in addition, the preparation method provided by the invention has the advantage of reducing energy waste in the production process of the PET automobile roof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automobile roof production, and more specifically, to an energy-saving PET automobile roof and a production process thereof. Background Art

[0002] As the automotive industry places increasing demands on lightweight and environmental performance, various new materials and technologies continue to emerge. Among them, foam materials made of high-performance plastics such as polyester (PET) have attracted widespread attention due to their excellent thermal and sound insulation properties. In the application of automotive interior parts, the ceiling is an important component, and the choice of its material directly affects the overall comfort and fuel economy of the vehicle. Traditionally, PU foam has dominated the automotive ceiling due to its good cushioning and processing flexibility, but in recent years, with the growing demand for sustainable production and reduced energy consumption, PET foam is gradually entering the market as a potential alternative.

[0003] PET foam can be produced by continuous extrusion, but after the molded PET foam material is molded and cooled, it needs to be compounded with other layer structures such as film and felt layer. During the compounding process, each layer needs to be heated, so that it needs to be repeatedly heated and cooled during the entire process, which increases energy consumption and reduces overall production efficiency. Summary of the invention

[0004] In order to reduce energy waste during the production process of PET automobile roofs, the present application provides an energy-saving PET automobile roof and a production process thereof.

[0005] In the first aspect, the present application provides an energy-saving PET automobile roof, which adopts the following technical solution: An energy-saving PET automobile roof comprises a fabric layer, an adhesive film, a glass fiber surface felt layer, a modified PET foam layer, a glass fiber surface felt layer, an adhesive film and a non-woven fabric layer which are connected in sequence. The modified PET foam layer comprises the following raw materials in parts by weight: 45-60 parts of polyester and 2.95-5.61 parts of a reinforcing agent, wherein the reinforcing agent comprises nanocellulose whiskers, modified carbon nanotubes and modified glass fibers.

[0006] By adopting the above technical scheme, the modified PET foam layer is prepared by mixing and foaming polyester and a reinforcing agent, so that the prepared modified PET foam layer has a smaller density and is lightweight, and the reinforcing agent formed by the composite of nanocellulose whiskers, modified carbon nanotubes and modified glass fibers can improve the strength of the modified PET foam layer, and at the same time can provide crystallization points for PET foaming, which is beneficial to the growth and stability of the foaming structure, and improves the pore uniformity and density of the modified PET foam layer. The modified PET foam layer is obtained using a continuous foaming device, and a glass fiber surface felt layer and an adhesive film are covered on both sides of the modified PET foam layer. The temperature of the modified PET foam layer after the foaming process can be used to heat the adhesive film to complete the compounding between the layers, and continuous production can be achieved at the same time, without repeated heating-cooling cycles, saving energy and improving production efficiency. The adhesive film of the top layer is covered by a recyclable release layer, and the bonding process of the fabric layer is completed after cooling, effectively realizing the protection of the adhesive film of the top layer and the protection of the fabric layer.

[0007] Preferably, the mass ratio of nanocellulose whiskers, modified carbon nanotubes and modified glass fibers in the reinforcing agent is (4.65-4.81):(0.54-0.59):(1.25-1.48).

[0008] By adopting the above technical scheme, nanocellulose whiskers are mixed with modified carbon nanotubes, and the modified carbon nanotubes can be carried on the nanofiber whiskers and dispersed together, which is beneficial to improve the dispersibility of the modified carbon nanotubes. At the same time, the raw materials in the reinforcing agent are all fibrous, and they are entangled and overlapped with each other to form a more complex micro-network structure with the polyester foam, thereby effectively improving the mechanical properties of the modified PET foam layer.

[0009] Preferably, the preparation method of the modified carbon nanotubes comprises the following steps: ultrasonically dispersing the carbon nanotubes in a mixture of ethanol and water, adjusting the pH to 9-10 with aqueous ammonia, adding tetraethoxysilane, reacting for 15-16 hours, centrifuging, separating, washing, and ultrasonically dispersing again in a mixture of ethanol and water, and freeze-drying to obtain the modified carbon nanotubes.

[0010] By adopting the above technical scheme, silicon dioxide is deposited on the surface of carbon nanotubes. Silicon dioxide can effectively improve the dispersibility of carbon nanotubes, and at the same time can improve the bonding degree between modified carbon nanotubes and polyester foam and the strength of modified carbon nanotubes, which is beneficial to the mixing and overlapping between modified carbon nanotubes and nanocellulose whiskers and modified glass fibers, thereby effectively improving the impact resistance of the modified PET foam layer.

[0011] Preferably, the modified carbon nanotubes are further subjected to the following treatment: the modified carbon nanotubes are heated to 150° C., preheated for 2 hours, and then vaporized hexamethyldisilazane is introduced to react for 45-50 minutes.

[0012] By adopting the above technical solution, the vaporized hexamethyldisilazane can modify the silicon dioxide deposited on the surface of the modified carbon nanotubes, effectively reduce the content of silanol groups, and improve its hydrophobicity, thereby further improving the dispersibility of the modified carbon nanotubes.

[0013] Preferably, the amount of hexamethyldisilazane added is 10.25-13.59 wt % of the modified carbon nanotubes.

[0014] By adopting the above technical solution, the amount of hexamethyldisilazane added is controlled, thereby effectively regulating the content of silanol groups on the surface of the modified carbon nanotubes. Too little addition will easily increase the content of silanol groups, and too much addition will easily lead to waste.

[0015] Preferably, the preparation method of the modified glass fiber comprises the following steps: mixing polydimethylsiloxane prepolymer, nano-silica and a curing agent, dispersing the mixture in toluene to obtain a mixed solution, immersing the glass fiber in the mixed solution, taking it out after soaking for 3-5 minutes, drying it naturally, and air-drying it at 120°C for 2 hours.

[0016] By adopting the above technical scheme, after the glass fiber is treated with a mixed solution, the surface is coated with polydimethylsiloxane, and nano-silicon dioxide is introduced, so that the roughness of the glass fiber surface is increased. Polydimethylsiloxane has good fiber adhesion, which can effectively improve the bonding degree between the modified glass fiber and the polyester foam, and can improve the connection strength between the modified glass fiber, nanocellulose whiskers and modified carbon nanotubes, thereby improving the effect of the reinforcing agent on improving the impact resistance of the automobile roof.

[0017] Preferably, the mass ratio of the polydimethylsiloxane to nano-silicon dioxide is (1.52-1.68):(0.98-1.05).

[0018] By adopting the above technical solution and controlling the amount of nano-silicon dioxide added, the roughness of the modified glass fiber surface is increased while retaining more pores, which is beneficial to the combination with polyester foam and also provides more growth sites for the foaming process of the PET foam layer.

[0019] In the second aspect, the present application provides a production process for an energy-saving PET automobile roof, which adopts the following technical solution: A production process for an energy-saving PET automobile roof comprises the following steps: mixing polyester and a reinforcing agent, extruding and granulating, foaming through a supercritical carbon dioxide continuous extrusion foaming device, attaching a glass fiber surface felt layer and an adhesive film to both sides of the extruded modified PET foam layer, attaching a non-woven fabric on one side, and attaching a release layer on the other side, after cooling together, peeling off the release layer, and attaching a fabric layer to obtain an energy-saving PET automobile roof.

[0020] By adopting the above technical scheme, the modified PET foam layer is continuously produced, and the temperature during the foaming process is used to attach the adhesive film and the glass fiber surface felt layer, and the adhesive film is heated to complete the composite process, thereby reducing the number of heating-cooling cycles and making full use of thermal energy.

[0021] In summary, this application has the following beneficial effects: 1. Since the modified PET foam layer in the present application is prepared by mixing and foaming polyester and a reinforcing agent, the prepared modified PET foam layer has a relatively small density and is lightweight, and the reinforcing agent formed by the composite of nanocellulose whiskers, modified carbon nanotubes and modified glass fibers can improve the strength of the modified PET foam layer, and can also provide crystallization points for PET foaming, which is beneficial to the growth and stability of the foaming structure, and improves the pore uniformity and density of the modified PET foam layer. The modified PET foam layer is obtained using a continuous foaming device, and an adhesive film and a glass fiber surface felt layer are covered on both sides of the modified PET foam layer. The adhesive film can be heated by utilizing the residual heat after the foaming process to complete the compounding between the layers, and continuous production can be achieved without repeated heating-cooling cycles, thereby saving energy and improving production efficiency.

[0022] 2. In the present application, nanocellulose whiskers are mixed with modified carbon nanotubes, and the modified carbon nanotubes can be carried on the nanofiber whiskers and dispersed together, which is beneficial to improve the dispersibility of the modified carbon nanotubes. At the same time, the raw materials in the reinforcing agent are all in fibrous form, and they are entangled and overlapped with each other to form a more complex microscopic network structure with the polyester foam, thereby effectively improving the mechanical properties of the modified PET foam layer.

[0023] 3. In the present application, silicon dioxide is deposited on the surface of carbon nanotubes. Silicon dioxide can effectively improve the dispersibility of carbon nanotubes, and at the same time can improve the bonding degree between carbon nanotubes and polyester foam and the strength of carbon nanotubes, which is beneficial to the mixing and overlapping between modified carbon nanotubes and nanocellulose whiskers and modified glass fibers, thereby effectively improving the impact resistance of the modified PET foam layer. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with embodiments. Preparation Examples 1-7 of Modified Carbon Nanotubes

[0025] Preparation Example 1 The preparation method of modified carbon nanotubes comprises the following steps: ultrasonically dispersing 0.49 g of carbon nanotubes in a mixed solution of 350 mL of ethanol and 50 mL of water, adjusting the pH to 9 with aqueous ammonia, adding 1 mL of tetraethoxysilane, reacting for 16 hours, centrifuging, separating, washing, and ultrasonically dispersing again in a mixed solution of 75 mL of ethanol and 5 mL of water, and freeze-drying to obtain modified carbon nanotubes.

[0026] Preparation Example 2 The preparation method of modified carbon nanotubes comprises the following steps: ultrasonically dispersing 0.57 g of carbon nanotubes in a mixed solution of 400 mL of ethanol and 55 mL of water, adjusting the pH to 10 with aqueous ammonia, adding 1.5 mL of tetraethoxysilane, reacting for 15 hours, centrifuging, separating, washing, and ultrasonically dispersing again in a mixed solution of 70 mL of ethanol and 3 mL of water, and freeze-drying to obtain modified carbon nanotubes.

[0027] Preparation Example 3 The preparation method of modified carbon nanotubes comprises the following steps: ultrasonically dispersing 0.52 g of carbon nanotubes in a mixed solution of 400 mL of ethanol and 60 mL of water, adjusting the pH to 9 with aqueous ammonia, adding 1.2 mL of tetraethoxysilane, reacting for 15 hours, centrifuging, separating, washing, and ultrasonically dispersing again in a mixed solution of 75 mL of ethanol and 4 mL of water, and freeze-drying to obtain modified carbon nanotubes.

[0028] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the modified carbon nanotubes are further treated as follows: the modified carbon nanotubes are heated to 150°C, preheated for 2 hours, and then vaporized hexamethyldisilazane is introduced and reacted for 45 minutes. The amount of hexamethyldisilazane added is 10.25 wt% of the modified carbon nanotubes.

[0029] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the modified carbon nanotubes are further treated as follows: the modified carbon nanotubes are heated to 150°C, preheated for 2 hours, and then vaporized hexamethyldisilazane is introduced and reacted for 50 minutes. The amount of hexamethyldisilazane added is 13.59 wt% of the modified carbon nanotubes.

[0030] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that in Preparation Example 6, the amount of hexamethyldisilazane added is 5.95 wt % of the modified carbon nanotubes.

[0031] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that in Preparation Example 7, the amount of hexamethyldisilazane added is 18.68 wt % of the modified carbon nanotubes.

[0032] Preparation Example 8-12 of Modified Glass Fiber

[0033] Preparation Example 8 The preparation method of modified glass fiber comprises the following steps: after polydimethylsiloxane prepolymer, nano-silicon dioxide and curing agent are mixed, the mass ratio of polydimethylsiloxane to nano-silicon dioxide is 1.52:0.98, the amount of curing agent added is 10wt% of polydimethylsiloxane, dispersed in toluene, and a mixed solution is obtained, the mass fraction of polydimethylsiloxane prepolymer in the mixed solution is 2%, and glass fiber is immersed in the mixed solution, taken out after immersion for 3 minutes, dried naturally, and air-dried at 120°C for 2 hours.

[0034] Preparation Example 9 The preparation method of modified glass fiber comprises the following steps: after polydimethylsiloxane prepolymer, nano-silicon dioxide and curing agent are mixed, the mass ratio of polydimethylsiloxane to nano-silicon dioxide is 1.68:1.05, the amount of curing agent added is 10wt% of polydimethylsiloxane, dispersed in toluene, and a mixed solution is obtained, the mass fraction of polydimethylsiloxane prepolymer in the mixed solution is 2%, and glass fiber is immersed in the mixed solution, taken out after immersion for 5 minutes, dried naturally, and air-dried at 120°C for 2 hours.

[0035] Preparation Example 10 The preparation method of modified glass fiber comprises the following steps: after polydimethylsiloxane prepolymer, nano-silicon dioxide and curing agent are mixed, the mass ratio of polydimethylsiloxane to nano-silicon dioxide is 1.62:1.02, the amount of curing agent added is 10wt% of polydimethylsiloxane, dispersed in toluene, and a mixed solution is obtained, the mass fraction of polydimethylsiloxane prepolymer in the mixed solution is 2%, and glass fiber is immersed in the mixed solution, taken out after immersion for 4 minutes, dried naturally, and air-dried at 120°C for 2 hours.

[0036] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 8 is that in Preparation Example 11, the mass ratio of polydimethylsiloxane to nano-silicon dioxide is 1.52:0.65.

[0037] Preparation Example 12 The difference between Preparation Example 12 and Preparation Example 8 is that in Preparation Example 12, the mass ratio of polydimethylsiloxane to nano-silicon dioxide is 1.52:1.95. Example

[0038] Example 1 An energy-saving PET automobile roof comprises a fabric layer, an adhesive film, a glass fiber surface felt layer, a modified PET foam layer, a glass fiber surface felt layer, an adhesive film and a non-woven fabric layer which are connected in sequence. The adhesive film is a modified PE film purchased from Shanghai Hansi Industrial Co., Ltd. The non-woven fabric is a spunlace non-woven fabric. The modified PET foam layer comprises the following raw materials in parts by weight: 45 kg of polyester and 2.95 kg of a reinforcing agent. The reinforcing agent comprises nanocellulose whiskers, modified carbon nanotubes and modified glass fibers. The mass ratio of the nanocellulose whiskers, modified carbon nanotubes and modified glass fibers in the reinforcing agent is 4.65:0.54:1.25. The modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 1, and the modified glass fibers are the modified glass fibers prepared in Preparation Example 8.

[0039] The production process of the energy-saving PET car roof comprises the following steps: mixing, extruding granulation, foaming through supercritical carbon dioxide continuous extrusion foaming equipment, attaching a glass fiber surface felt layer and an adhesive film on both sides of the extruded modified PET foam layer, and attaching a non-woven fabric layer on one side and a release layer on the other side. After cooling together, the release layer is peeled off and the fabric layer is attached to obtain the energy-saving PET car roof.

[0040] Example 2 An energy-saving PET automobile roof comprises a fabric layer, an adhesive film, a glass fiber surface felt layer, a modified PET foam layer, a glass fiber surface felt layer, an adhesive film and a non-woven fabric layer which are connected in sequence. The adhesive film is a modified PP film purchased from Shanghai Hansi Industrial Co., Ltd. The non-woven fabric is a spunbonded non-woven fabric. The modified PET foam layer comprises the following raw materials in parts by weight: 60 kg of polyester and 5.61 kg of a reinforcing agent. The reinforcing agent comprises nanocellulose whiskers, modified carbon nanotubes and modified glass fibers. The mass ratio of the nanocellulose whiskers, modified carbon nanotubes and modified glass fibers in the reinforcing agent is 4.81:0.59:1.48. The modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 2, and the modified glass fibers are the modified glass fibers prepared in Preparation Example 9.

[0041] The production process of the energy-saving PET car roof comprises the following steps: mixing, extruding granulation, foaming through supercritical carbon dioxide continuous extrusion foaming equipment, attaching a glass fiber surface felt layer and an adhesive film on both sides of the extruded modified PET foam layer, and attaching a non-woven fabric layer on one side and a release layer on the other side. After cooling together, the release layer is peeled off and the fabric layer is attached to obtain the energy-saving PET car roof.

[0042] Example 3 An energy-saving PET automobile roof comprises a fabric layer, an adhesive film, a glass fiber surface felt layer, a modified PET foam layer, a glass fiber surface felt layer, an adhesive film and a non-woven fabric layer which are connected in sequence. The adhesive film is a copolymerized PA film purchased from Tianyang New Materials Shanghai Science and Technology Co., Ltd. The non-woven fabric is a short-filament hot-rolled cloth. The modified PET foam layer comprises the following raw materials in parts by weight: 55 kg of polyester and 4.25 kg of a reinforcing agent. The reinforcing agent comprises nanocellulose whiskers, modified carbon nanotubes and modified glass fibers. The mass ratio of the nanocellulose whiskers, modified carbon nanotubes and modified glass fibers in the reinforcing agent is 4.72:0.56:1.38. The modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 3, and the modified glass fibers are the modified glass fibers prepared in Preparation Example 10.

[0043] The production process of the energy-saving PET car roof comprises the following steps: mixing, extruding granulation, foaming through supercritical carbon dioxide continuous extrusion foaming equipment, attaching a glass fiber surface felt layer and an adhesive film on both sides of the extruded modified PET foam layer, and attaching a non-woven fabric layer on one side and a release layer on the other side. After cooling together, the release layer is peeled off and the fabric layer is attached to obtain the energy-saving PET car roof.

[0044] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the mass ratio of nanocellulose whiskers, modified carbon nanotubes and modified glass fibers in the reinforcing agent is 4.65:1.52:0.58.

[0045] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the mass ratio of nanocellulose whiskers, modified carbon nanotubes and modified glass fibers in the reinforcing agent is 4.65:0.25:2.68.

[0046] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 4.

[0047] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 5.

[0048] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 6.

[0049] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the modified carbon nanotubes are the modified carbon nanotubes prepared in Preparation Example 7.

[0050] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the modified glass fiber is the modified glass fiber prepared in Preparation Example 11.

[0051] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the modified glass fiber is the modified glass fiber prepared in Preparation Example 12.

[0052] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, no reinforcing agent is added to the modified PET foam layer.

[0053] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, an equal amount of nanocellulose whiskers is used instead of the reinforcing agent.

[0054] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, an equal amount of modified carbon nanotubes is used instead of the reinforcing agent.

[0055] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, an equal amount of modified glass fiber is used instead of the reinforcing agent.

[0056] Performance testing According to the raw materials and production processes of Examples 1-11 and Comparative Examples 1-4, automobile roofs were manufactured, and the impact strength of the automobile roofs was tested using a stamping tester, and the results are recorded in Table 1.

[0057] Table 1 Performance test of car roof project Impact strength / MPa Example 1 25.68 Example 2 27.12 Example 3 26.58 Example 4 22.91 Example 5 23.25 Example 6 27.68 Example 7 28.10 Example 8 25.68 Example 9 27.18 Example 10 22.61 Embodiment 11 23.01 Comparative Example 1 18.26 Comparative Example 2 20.15 Comparative Example 3 21.26 Comparative Example 4 20.92 It can be seen from Examples 1-3 and Table 1 that the automobile roofs prepared in Examples 1-3 have good impact strength. In the automobile roofs of Examples 1-3, a continuously extruded modified PET foam layer is used as a core layer, which is coated with an adhesive film and a glass fiber surface felt layer to form a composite automobile roof. The modified PET foam layer can effectively achieve lightweight automobile roofs. At the same time, a reinforcing agent is added to the modified PET foam layer. Nanocellulose whiskers, modified carbon nanotubes and modified glass fibers are all fibrous, and the entanglement and overlap with each other can provide crystallization points for PET foaming, which is beneficial to the foaming of PET. At the same time, the pore uniformity and density of the modified PET foam layer can be improved. The reinforcing agent can form a complex network structure with the polyester foam, thereby effectively improving the impact resistance of the modified PET foam layer, and then improving the impact resistance of the automobile roof.

[0058] The modified carbon nanotubes deposit silicon dioxide on the surface of the carbon nanotubes. The silicon dioxide can effectively improve the dispersibility of the carbon nanotubes, and at the same time can improve the bonding degree between the modified carbon nanotubes and the polyester foam, which is beneficial to the mixing and overlapping of the modified carbon nanotubes with the nanocellulose whiskers and the modified glass fibers. The modified glass fibers are coated with polydimethylsiloxane on the surface of the glass fibers, and nano-silicon dioxide is introduced to improve the roughness of the glass fiber surface. Polydimethylsiloxane has good fiber adhesion, which can effectively improve the bonding strength between the modified glass fibers and the polyester foam, and at the same time improve the connection strength between the reinforcing agents, which is beneficial to improving the reinforcing agent's improvement effect on the impact resistance of the automobile roof.

[0059] Compared with Example 1-3, the impact strength of the automobile roof prepared by Example 4-5 and Comparative Example 1-4 decreased. Example 4-5 changed the mass ratio of nanocellulose whiskers, modified carbon nanotubes and modified glass fibers in the reinforcing agent. No reinforcing agent was added in Comparative Example 1, only nanocellulose whiskers were added in Comparative Example 2, only modified carbon nanotubes were added in Comparative Example 3, and only modified glass fibers were added in Comparative Example 4. Compared with Example 1-3, the impact strength of the automobile roof of Comparative Examples 2-4 decreased, indicating that there is a synergistic effect among nanocellulose whiskers, modified carbon nanotubes and modified glass fibers. The reinforcing agent formed by compounding the three in a certain mass ratio can effectively improve the impact strength of the modified PET foam layer. When the composition and mass ratio change, the synergistic effect between nanocellulose whiskers, modified carbon nanotubes and modified glass fibers is weakened, and the reinforcing effect of the reinforcing agent on the modified PET foam layer decreases.

[0060] Compared with Examples 1-3, the impact resistance of the automobile roof prepared in Example 6-7 is improved. During the preparation of the modified carbon nanotubes used in Example 6-7, the modified carbon nanotubes are modified using vaporized hexamethyldisilazane. Nano-silicon dioxide is deposited on the surface of the carbon nanotubes, which can effectively improve the bonding degree between the modified carbon nanotubes and the polyester foam and the strength of the modified carbon nanotubes. The modification treatment with vaporized hexamethyldisilazane can reduce the silanol groups on the surface of the modified carbon nanotubes and improve their hydrophobicity, thereby further improving the dispersibility and bonding of the modified carbon nanotubes.

[0061] Compared with Examples 6-7, the impact strength of the car roof prepared in Example 8 decreased, while the impact strength of the car roof prepared in Example 9 did not change significantly. When preparing the modified carbon nanotubes used in Examples 8-9, the amount of hexamethyldisilazane added was reduced in Example 8, which increased the silanol content on the surface of the modified carbon nanotubes in Example 8, reduced hydrophobicity, and weakened dispersibility. However, in Example 9, the amount of hexamethyldisilazane added was increased, but the performance of the prepared car roof did not change significantly, indicating that the amount of hexamethyldisilazane used was excessive and wasted.

[0062] Compared with Example 1-3, the impact strength of the automobile roof prepared in Example 10-11 is reduced. When preparing the modified glass fiber used in Example 10-11, the mass ratio of polydimethylsiloxane to nano-silicon dioxide is changed, and the addition amount of nano-silicon dioxide is controlled, so that the roughness of the surface of the modified glass fiber increases. When the addition amount of nano-silicon dioxide is reduced, the roughness decreases, and the bonding between the modified glass fiber and the polyester foam decreases. When the addition amount of nano-silicon dioxide is increased, the pores of the polyester foam are easily blocked, thereby reducing its impact resistance.

[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An energy-saving PET car roof, characterized in that: The invention comprises a fabric layer, an adhesive film, a glass fiber surface felt layer, a modified PET foam layer, a glass fiber surface felt layer, an adhesive film and a non-woven fabric layer which are connected in sequence. The modified PET foam layer comprises the following raw materials in parts by weight: 45-60 parts of polyester and 2.95-5.61 parts of a reinforcing agent, wherein the reinforcing agent comprises nano cellulose whiskers, modified carbon nanotubes and modified glass fibers.

2. The energy-saving PET automobile ceiling according to claim 1, characterized in that: The mass ratio of the nanocellulose whiskers, the modified carbon nanotubes and the modified glass fibers in the reinforcing agent is (4.65-4.81):(0.54-0.59):(1.25-1.48).

3. The energy-saving PET automobile ceiling according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: ultrasonically dispersing the carbon nanotubes in a mixed solution of ethanol and water, adjusting the pH to 9-10 with ammonia water, adding tetraethoxysilane, reacting for 15-16 hours, centrifuging, separating, washing, ultrasonically dispersing again in a mixed solution of ethanol and water, and freeze-drying to obtain the modified carbon nanotubes.

4. The energy-saving PET automobile ceiling according to claim 3 is characterized in that: The modified carbon nanotubes are further treated as follows: the modified carbon nanotubes are heated to 150° C., preheated for 2 hours, and then vaporized hexamethyldisilazane is introduced to react for 45-50 minutes.

5. The energy-saving PET automobile ceiling according to claim 4 is characterized in that: The amount of hexamethyldisilazane added is 10.25-13.59 wt % of the modified carbon nanotubes.

6. The energy-saving PET automobile ceiling according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: mixing polydimethylsiloxane prepolymer, nano silicon dioxide and curing agent, dispersing the mixture in toluene to obtain a mixed solution, immersing the glass fiber in the mixed solution, taking it out after immersion for 3-5 minutes, drying it naturally, and air-drying it at 120° C. for 2 hours.

7. The energy-saving PET automobile ceiling according to claim 6, characterized in that: The mass ratio of the polydimethylsiloxane to the nano-silicon dioxide is (1.52-1.68):(0.98-1.05).

8. The production process of an energy-saving PET automobile ceiling according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polyester and the reinforcing agent are mixed, extruded into granules, and foamed through a supercritical carbon dioxide continuous extrusion foaming device. A glass fiber surface felt layer and an adhesive film are attached to both sides of the extruded modified PET foam layer, and a non-woven fabric layer is attached to one side and a release layer is attached to the other side. After cooling together, the release layer is peeled off and the fabric layer is attached to obtain an energy-saving PET car roof.

Citation Information

Patent Citations

  • Automobile ceiling and manufacturing method thereof

    CN109517366A

  • Low gram weight antibacterial automobile interior decoration ceiling sheet and production method thereof

    CN110696442A

  • Low-odor dry ceiling and manufacturing method thereof

    CN119427859A

  • Environment-friendly automobile interior ceiling and preparation method thereof

    CN119610817A

  • Fiber reinforced thermoplastic composite material automotive interior ceiling and preparation method thereof

    CN119610818A

Cited By

  • Environment-friendly composite material for automobile and preparation method of environment-friendly composite material

    CN120269897A